تشكلات النزعة الدرامية في شعر ذي الرمّة - مي, أحمد يوسف; عمر العزام, صفاء (Université de M'sila, 2017)
اهتم البحث بد ا رسة تشّكُّلات النزعة الد ا رمية في شعر ذي الرمة، في ثلاثة محاور؛ الموقف الد ا رمي؛ والحوار الخارجي؛ والداخلي؛ والمستوى الخطابي. ووظف عنصر الحوار في أشعاره بنوعيه: الداخلي، الخارجي، فمزج بينهما في إطار السرد القصصي، وأسهم كثي اً ر في إكساب الشعر مرونة د ا رمية. وسعى إلى الم ا زوجة بين صيغة الخطاب السردي الحكائي، وصيغة الخطاب الد ا رمي)الحوار(.
This research investigated the forming of Drama way in the poetry of Dhi- Al-Rimma, in three parts, The drama situation.Dho- Al-Rimma could collect, in his poems, the song and drama .Dho-Al-Rimma employed the both types of dialogue in his poems the internal dialogue and the external dialogue, so he mixed the drama dialogue and monologue in the frame of narration, and contributed in the drama flexibility in the poem .Tho-Al-Rimma tend to duplicate the narrative discourse form that represented in the story elements, and the drama discourse form that represented in the dialogue.
Keywords: الد ا رما، التصوير الد ا رمي .الد ا رمية. ( drama, dramatic configuration The Alremmah poems, and dramatiztion )